My man, Michael - Foster, Lori 1958- (Berkley, 2009)
When a car accident destroys his dream of becoming an SBC fighting champion, Michael "Mallet" Manchester believes that his life is over until Kaylie Raine appears and offers him an extraordinary challenge.